ANALISIS PENGARUH TEMPERATUR PENDINGINAN PADA LITHIUM-BATTERY BOX TERHADAP PROSES CHARGING PADA SKUTER TENAGA SURYA - Arindrian Kurnia; Asrori Asrori (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
When the battery is used, it will generate heat due to chemical processes and external factors like sunlight that make the battery hot on the solar panel-based transport e-scooter. Indirectly, the battery also receives heat from the surrounding environment. Battery temperature also affects the performance, efficiency, and performance of the battery, so to maintain battery temperature, cooling is needed. This study aims to determine the variation of battery cooling temperature on the charging power of LiFePO4 batteries on e-scooters with solar panels. This research method is carried out by making a battery-cooling device as a box with active cooling using a cooling fan to cool the battery inside. After that, it makes a management and monitoring tool for the battery cooling system to regulate and measure the temperature of the ESP32-based battery. After conducting research and data processing, it can be concluded that the advantages of installing a LifePO4 battery cooling system on an e-scooter using solar panels can increase charging power. From all the data obtained, the temperature when charging at 25oC has a power that is 19% greater than the 35oC temperature on the battery